SOCIAL PRACTICES AND ETHNIC IDENTITY OF BEKWARRA MIGRANT WORKERS IN ONDO AND NASARAWA STATES, NIGERIA, 1940-2015 - Joseph Okuta Ajor; Godwin Oko Ushie; Julius Simon Odey (Social Sciences, Humanities and Education Journal (SHE Journal), 2021)
Bekwarra migrants, wherever they settle in good numbers, engage in undying social practices that maintain their distinct ethnic identity. Such social practices include cultural dance, traditional marriage, New Yam Festivals, Age Grade system, burial rites and work songs. These practices perform functions that range from maintenance of their ethnic identity, socialization and enculturation of their children, social cohesion and literary aesthetics. This paper, using functionalism as its theoretical framework, examines such practices as are obtained in Ondo State in South West geographical zone and Nasarawa State in North Central geographical zones of Nigeria where they form clusters of populations that play prominent roles in socio-economic and political roles in their host states. The paper concludes that the maintenance of ethnic identity among the rural migrants in Nigeria is a social security system that served the purpose of giving them self-identity in a hyper, multi-ethnically complex country.